GAMBARAN PENGETAHUAN DAN SIKAP TERHADAP PEMENUHAN SYARAT KUALITAS AIR MINUM PADA MASYARAKAT YANG TINGGAL DI BANTARAN SUNGAI KELURAHAN TERUSAN KECAMATAN MEMPAWAH HILIR - Juwairiyah Dzakiyyah; Bambang Supraptono; Susilawati, Susilawati (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Pontianak, 2024)
Diarrhea in Mempawah Hilir is 5 times the national figure with a prevalence of 9.8%, while the prevalence rate in Mempawah Hilir in 2021 is 42%. One of the factors causing the high number of diarrhea cases is inadequate drinking water sources that are consumed inappropriately. The aim of this research is to describe knowledge and attitudes towards fulfilling drinking water quality requirements in communities living on the banks of the river of the Kelurahan Terusan, Kecamatan Mempawah Hilir. The method used in this research is a descriptive method by describing the knowledge and attitudes of the people who live in the riverbank area Kelurahan Terusan, Kecamatan Mempawah Hilir. The population of people living along the river is 539 families. The sample used in this research was 84 heads of families (KK). The results obtained in this research were that 32% of people had good knowledge, 52% had sufficient knowledge, and 16% had poor knowledge. People who have a good attitude are 95.24%, and 4.76% are sufficient. The conclusion of this research is that the people who live on the riverbanks of Kelurahan Terusan Kecamatan Mempawah Hilir 52% knowledge and 95.24% good attitudes.